T cell expansion from umbilical cord blood without thymic stroma cells after stimulation with SCF, IL-7, AND IL-2 - Fischer, Johannes; Sabagh, Fatemeh; Kogler, Gesine; Migliaccio, Anna R.; Wernet, Peter (Archives of Advances in Biosciences, 2010)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0in; margin-right:0in; margin-bottom:10.0pt; margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:Arial; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-ascii-font-family:Calibri; mso-hansi-font-family:Calibri; mso-bidi-font-family:Arial; @page Section1 size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>We analyzed in vitro expansion and differentiation of T progenitor cells from umbilical cord blood in the absence of thymic epithelium. The expansion setup is performed in the presence of SCF, IL-7 , and IL -2 with autologous serum .Using CBMCs as initial source , we compared the growth kinetics of several cell populations in either whole CBMC or CD34+ -enriched-, as well as in CD3CD4CD8-depleted expansion assays by FACS analysis. After 11 days of culture, cell increase values were about 7 fold for CD3+, 6 fold for CD3+CD4+, 7 fold for CD3+CD8+, 4fold for CD3+CD56, 6fold for CD56+, and 0.2 fold for CD34+. We characterized the developmental state of these cell populations by RT –PCR analysis of the lymphoid differentiation markers RAG-1 and pre T-Alpha. In all samples , transcripts of both markers could be detected from day 0 though day 11, however , in case of pre – T-Alpha, nested PCR was always required , indicating lower expression . These findings; therefore, demonstrate that T-cell differentiation events (as opposed to mere expansion) do occur in stroma cell free expansion assays.